Anal Fistula Principles and Management - Abcarian, Herand (Springer New York : Imprint: Springer, 2014)
Anal Fistula: Principles and Management provides a comprehensive and state of the art review of major issues specific and related to the treatment of anal fistulas. An important section of the book covers the large number of alternative procedures which have been developed in the last two decades. Needless to say, none of these procedures have been uniformly successful, otherwise there would be no need for all the different operations. The book addresses each alternative procedure, discusses the benefits of each procedure, includes the most up-to-date results. Other important chapters cover the causes and failure of treatment and operations for fistulas. Also included is a Cochrane Review of all available randomized controlled trials with levels of evidence culled from the literature.       Written by specialists in their respective fields, Anal Fistula: Principles and Management fills a void in available texts on a subject matter very commonly encountered by surgeons, physicians and specialists.   .